Re-Evaluating Women's Page Journalism in the Post-World War II Era Celebrating Soft News - Voss, Kimberly Wilmot (Springer International Publishing, 2018)
Re-Evaluating Women's Page Journalism in the Post-World War II Era tells the stories of significant women's page journalists who contributed to the women's liberation movement and the journalism community. Previous versions of journalism history had reduced the role these women played at their newspapers and in their communities-if they were mentioned at all. For decades, the only place for women in newspapers was the women's pages. While often dismissed as fluff by management, these sections in fact documented social changes in communities. These women were smart, feisty and ahead of their times. They left a great legacy for today's women journalists. This book brings these individual women together and allows for a broader understanding of women's page journalism in the 1950s and 1960s. It details the significant roles they played in the post-World War II years, laying the foundation for a changing role for women.